Triglyceride to high-density lipoprotein cholesterol ratio was negatively associated with relative grip strength in older adults: a cross-sectional study of the NHANES database - Huang, Yan; Liao, Jian; Liu, Yang (Frontiers in Public Health, 2023)
Aim: This study aims to explore the association between triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio and relative grip strength in old adults in order to provide some reference for the prevention and control of the sarcopenia.: Demographic and clinical data of 1,404 individuals aged ≥60 years old were extracted from the National Health and Nutrition Examination Survey (NHANES) database in 2011-2014 in this cross-sectional study. The definition of relative grip strength was the sum of the largest reading from each hand/body mass index (BMI)ratio. We used weighted univariate linear regression and stepwise regression analysis to screen the covariates. Weighted univariate and multivariate linear regression analyses were used to explore the association between TG/HDL-C ratio and the relative grip strength. We also explored this relationship in subgroups of gender, diabetes mellitus (DM), cardiovascular disease (CVD) and arthritis. The evaluation index was β with 95% confidence intervals (CIs).Results: Totally 1,306 old adults were eligible. After adjusting for the covariates including age, gender, race, marital status, physical activity, DM, CVD, arthritis and chronic kidney disease (CKD), we found that TG/HDL-C ratio was negatively linked to the relative grip strength (all P<0.05). Furthermore, the increased TG/HDL-C ratio was also negatively related to the decreased relative grip strength in those who were female, not having DM, and having CVD (all P<0.05).With the increase of TG/HDL-C ratio, the relative grip strength of old adults decreased significantly, indicating that TG/HDL-C ratio could be closely Relative grip strength and TG/HDL-C ratio levels in old adults 3 monitored in old population due to it may be associated with the prevention and control 39 of the sarcopenia.